Musica e società, 2. Dal 1640 al 1830, a cura di Paolo Fabbri, Alessandro Roccatagliati e Paolo Russo; e volume 3. Dal 1830 al 2000, a cura di Virgilio Bernardoni e Paolo Fabbri - Della Seta, Fabrizio (Musica Docta, 2016)
Musica e Storia is a project for a textbook, conceived and supervised by Paolo Fabbri. The second volume consists of six chapters and addresses the period between 1640, which marks the rise of public opera theatre, and 1830, when the Romantic sensibility had become established. The third volume spans the period from 1830 to today, and includes two parts, dedicated to the years before and after the watershed date of 1920. The first volume has already been examined by Dinko Fabris in this periodical (III, 2013, pp. 139-142).